2020
DOI: 10.31002/vigor.v5i2.3062
|View full text |Cite
|
Sign up to set email alerts
|

Komposisi Jenis Invasive Aliens Species (Ias) Di Kebun Raya Baturraden, Jawa Tengah

Abstract: Ecologically Invasive Aliens Species (IAS) poses a particular threat to the conservation area that is a biodiversity sanctuary, Baturraden Botanical Garden (KRB). The purpose of this research is to find out the composition of IAS in KRB. This method of research is a survey method with purposive random sampling. Observation and prosecution is done by dividing krb into 10 plots. Information on the introduction process as well as conservation strategy recommendations is obtained through library studies and interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…Pengelolaan gulma ini dapat dilakukan dengan mitigasi dan pemeliharaan berkala. Pengendalian dapat dilakukan melalui eradikasi (Sulistiyowati et al, 2020). Suku dengan jumlah terbanyak selanjutnya dari Commelinaceae yang terdiri dari Murdannia nudiflora (L.) Brenan dan Commelina diffusa Burm.f.…”
Section: Hasil Dan Pembahasanunclassified
“…Pengelolaan gulma ini dapat dilakukan dengan mitigasi dan pemeliharaan berkala. Pengendalian dapat dilakukan melalui eradikasi (Sulistiyowati et al, 2020). Suku dengan jumlah terbanyak selanjutnya dari Commelinaceae yang terdiri dari Murdannia nudiflora (L.) Brenan dan Commelina diffusa Burm.f.…”
Section: Hasil Dan Pembahasanunclassified
“…However, only a few were woody tree and shrub species, such as Mimosa pigra L., Clibadium surinamense L., Hyptis capitata Jacq., Clidemia hirta (L.) D.Don, and M. malabathricum, while the remaining species were from the Asteraceae family who are generally herbaceous. Sulistiyowati et al (2020) found 13 invasive species, of which one was a tree (Schima wallichii (DC.) Korth.…”
Section: Invasive Trees and Shrubsmentioning
confidence: 99%
“…Penelitian ini diharapkan dapat memberikan informasi kepada pihak kebun raya terkait dengan pencegahan dan penanggulangan tumbuhan yang bersifat invasif. Kawasan konservasi yang sehat adalah kawasan yang rendah populasi tumbuhan invasif bahkan terbebas dari kehadiran tumbuhan invasive (Bravo et al, 2019), sehingga tidak mengganggu menajemen pengelolaan lahan (Macic et al, 2018) dan tidak berdampak ke aspek lainnya (Sulistiyowati et al, 2020).…”
Section: Pendahuluanunclassified